1996
DOI: 10.1073/pnas.93.20.11259
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic male-sterile plant induced by an unedited atp9 gene is restored to fertility by inhibiting its expression with antisense RNA.

Abstract: We have previously shown that the expression of an unedited atp9 chimeric gene correlated with malesterile phenotype in transgenic tobacco plant. To study the relationship between the expression of chimeric gene and the male-sterile trait, hemizygous and homozygous transgenic tobacco lines expressing the antisense atp9 RNA were constructed. The antisense producing plants were crossed with a homozygous male-sterile line, and the Fl progeny was analyzed. The offspring from crosses between homozygous lines produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0
1

Year Published

1998
1998
2011
2011

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 29 publications
3
28
0
1
Order By: Relevance
“…These results thus suggest that the cis-elements have evolved between the two plant species, and it thus can be assumed that also the respective trans-elements have changed and presently differ between the pea and the cauliflower. Nevertheless, the basic mode of editing site specification has of necessity been conserved in evolution between these two flowering plants, since both definitely require this C-to-U alteration for a functional mitochondrial ATPase (Hernould et al 1993;Zabaleta et al 1996).…”
Section: Discussionmentioning
confidence: 99%
“…These results thus suggest that the cis-elements have evolved between the two plant species, and it thus can be assumed that also the respective trans-elements have changed and presently differ between the pea and the cauliflower. Nevertheless, the basic mode of editing site specification has of necessity been conserved in evolution between these two flowering plants, since both definitely require this C-to-U alteration for a functional mitochondrial ATPase (Hernould et al 1993;Zabaleta et al 1996).…”
Section: Discussionmentioning
confidence: 99%
“…As detailed above male sterility was obtained by engineering plants able to synthesize an unedited mitochondrial protein in the cytosolic ribosomes which was further addressed to the mitochondria. Our approach to restore fertility was based on the antisense strategy (Zabaleta et al, 1996). The working hypthesis was that crossing the male-sterile plants produced as described above with plants expressing the same mRNA but in the antisense orientation should lead to the formation of a dsRNA.…”
Section: Recovering the Fertility Of Artificially Created Malesterilementioning
confidence: 99%
“…Our approach to restore fertility was based on the antisense strategy (Zabaleta et al, 1996). The working hypthesis was that crossing the male-sterile plants produced as described above with plants expressing the same mRNA but in the antisense orientation should lead to the formation of a dsRNA.…”
mentioning
confidence: 99%
“…Pollen abortion was induced after transforming an incompletely edited atp9 gene in tobacco; however, normal fertility remained the same after transforming a completely edited atp9 gene in tobacco (Hernould et al, 1993). Further study showed that the fertility of tobacco could be restored by inhibiting expression of the incompletely edited atp9 gene (Zabaleta et al, 1996). In addition, CMS was obtained by transforming unedited atp9 gene into tobacco (Araya et al, 1998).…”
Section: Protein Trans-membrane Structure Predictionmentioning
confidence: 82%